Comparative Evaluation of RBPT and I-ELISA in the Diagnosis of Brucellosis in Small Ruminants and the Analysis of Associated Risk Factors - Aafiya, Shaik; Swetha, Chinta Siva; Babu A, Jagadeesh; Kavitha K, Lakshmi; Putturu, Ramya; Yasarla, Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Brucellosis is a neglected bacterial zoonotic disease affecting livestock and humans in developing countries. Hence, the present study aimed to determine the seroprevalence of Brucellosis and to assess the risk factors associated with the occurrence of Brucellosis in small ruminants of Tirupati district, Andhra Pradesh, India. A total of 450 sera samples (245 from sheep and 205 from goats) were screened for Brucella antibodies by Rose Bengal Plate Test (RBPT) and by I-ELSIA method with an Indirect ELISA kit developed and standardized at NIVEDI, Yelahanka, Bengaluru. Out of 450 sera samples, RBPT detected none of the Brucella antibodies while 17 samples (3.77%) found the presence of Brucella antibodies by I-ELISA in sheep and goats. It was shown that sheep (4.08%) had a higher infection prevalence than goats (3.41%).  In conclusion, I-ELISA was found to be most sensitive and specific serological test in the diagnosis of small ruminant Brucellosis than RBPT. Risk factor analysis revealed age, abortion history, vaginal discharge, multiparity, mixed farming (sheep and goat together), migratory herds, large herd size, sharing of ram/bucks, place of disposal of aborted materials, presence of dogs near farm surroundings, and assisting during lambing were all found to have positive statistical association with the seroprevalence of Brucellosis in sheep and goats in the study region. Whereas, sharing of buck, mode of procurement of animals, disposal of aborted materials, and assisting during kidding were found non- significant factors and were not associated with the seroprevalence of the disease in goats.
Keywords: Awareness; Brucella; I-ELISA; RBPT; Risk factors; Sheep and goats